Flexible Bronchoscopic Removal of a Forgotten Intrabronchial Foreign Body - Dhungana, Ashesh; Thapa, Ajit (Journal of Nepal Health Research Council, 2019)
Foreign body aspiration is uncommon in adults and the diagnosis may be delayed in the elderly, as many fail to provide a history of choking during initial evaluation. Flexible bronchoscopy is a useful tool for foreign body extraction from the tracheobronchial tree in selected cases. A Sixty-two year old male presented with history of cough, purulent sputum and intermittent hemoptysis. CT scan of the thorax demonstrated a radio-dense foreign body in the bronchus intermedius causing focal narrowing. Flexible fiberoptic bronchoscopy revealed a glistening white bone in the distal bronchus intermedius which was successfully grasped with the flexible forceps and extracted via the oral route with the bronchoscope. Keywords: Elderly; flexible bronchoscopy; foreign body aspiration.